THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN TEACHING INFORMATICS - Haqberdiyev Bahrom Bobonazarovich (Ecominds Press, 2026)
This article analyzes the role of artificial intelligence (AI) technologies in the teaching of informatics. The study examines the concept of AI, its pedagogical potential, and the methods of its application in the educational process. Using various examples, it describes how AI capabilities—such as adaptive learning systems, virtual tutors, chatbots, and automated assessment systems—contribute to the effective teaching of informatics. Furthermore, the article analyzes technical, qualification, and information security challenges arising from the implementation of AI technologies and presents future prospects. The article is aimed at developing informatics education based on modern information technologies and exploring ways to effectively utilize AI tools.
Keywords: Informatics education, artificial intelligence, adaptive learning systems, virtual tutor, automated assessment.